CORRELATION STUDIES IN EARLY SEGREGATING GENERATION IN GROUNDNUT (ARACHIS HYPOGAEA L.) - SHREYA; R. P VASANTHI; AINMISHA; K. SRIVASTAVA (The Bioscan, 2015)
The present experiment was conducted to study correlation for yield and yield contributing characters in F 3 generation derived from four crosses of groundnut (involving parents; ICGV 05163, ICGV 06045, ICGV 93261, TCGS 1043 and TCGS 913; TCGS 1043 was used as common female parent). Correlation analysis indicated that yield (mature pod weight per plant) was significant and positively associated with number of primary branches per plant (PB) (0.273 to 0.401), plant height per plant (PH in cm) (0.179 to 0.404), pegs number per plant (PN) ( 0.478 to 0.613), total biomass per plant (TB in g) (0.779 to 0.819), shoot weight per plant (SW in g) (0.448 to 0.542), root weight per plant (RW in g) (0.311 to 0.458), number of mature pods per plant (MP) (0.742 to 0.853), number of immature pods per plant (IM) (0.161to 0.387) , harvest index (HI in %) (0.435 to 0.572) and kernel weight per plant (KW in g) (0.950 to 0.980) for all the four crosses. Hence, suggesting that all the above mentioned characters may be considered as prime traits during the course of selection to have the higher potential yields in case of groundnut.